On the calibration of the relation between geometric albedo and polarimetric properties for the asteroids - Cellino, A. (2015)
We present a new extensive analysis of the old problem of finding a satisfactory calibration of the relation between the geometric albedo and some measurable polarization properties of the asteroids. To achieve our goals, we use all polarimetric data at our disposal. For the purposes of calibration, we use a limited sample of objects for which we can be confident to know the albedo with good accuracy, according to previous investigations of other authors. We find a new set of updated calibration coefficients for the classical slope–albedo relation, but we generalize our analysis and we consider also alternative possibilities, including the use of other polarimetric parameters, one being proposed here for the first time, and the possibility to exclude from best-fitting analyses the asteroids having low albedos. We also consider a possible parabolic fit of the whole set of data.